Aktywność powiatów woj. kujawsko-pomorskiego w zakresie pozyskiwania środków ze Zintegrowanego Programu Operacyjnego Rozwoju Regionalnego (ZPORR) - Zajdel, Małgorzata (Activity of Powiats in Kujawy and Pomorze Voivodship in the Context of Funds Rising from the Integrated Program of Operating Regional Development (IPORD), 2005)
In the paper assessment of level of activity of powiats in the scope of applications put in the frame of ZPORR Program in Pomorze and Kujawy voivodship is made. Benefactors participating in the pre-accession SAPARD Program confirmed its high level of skills in absorption of the EU funds in the frame of IPORD in the first period of the budgeting between 2004-2006.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 440-445